Lew, który nie ryczy? Obraz lwa u Homera - Miziur-Moździoch, Maja (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The article is devoted to the presentation of the image of the lion in the Homeric epics. The paper does not profess to create a study of the Homeric metaphor or comparisons related to lions, but rather it is geared towards those interested in fauna in the ancient world. It aims to produce a complete picture of the lion in Homer: what it looks like, how people see it, what habits it has. The article will also aim to answer the question whether the lion of Homer’s times, which we meet in his epics, was indeed a part of everyday life for Greek people, or whether it was actually a creation adapted from the Near Eastern or Mycenean tradition.
Keywords: epika; Homer; Iliada; Odyseja; lew